The Problem of solid waste in Al-Amarah City and its environmental impacts (Journal of Misan Researches, 2023)
Amara city, like other third-world cities, suffers from a growing population, happen together increasing in the amount of waste generated by diverse population activities. It is a true problem and a major national challenge under difficult circumstances and low possibilities of dealing with them. The continuous increase of waste and its chaotic accumulation, whether in neighborhoods or in a sanitary landfill, create many risks to the environment and public health. It may become an important economic resource if it is handled properly through recycling it and making use of its recyclable and reusable organic and mineral components.